PELAKSANAAN PROGRAM KESEHATAN PADA KOMUNITAS REMAJA: EDUKASI MANFAAT GIZI DALAM MENDUKUNG PERTUMBUHAN DAN PERKEMBANGAN TUBUH MANUSIA - Maria Floriana Ping; Fransiska Novita Sari (JPMK : Jurnal Pengabdian Masyarakat Kasih Published by Unit Penelitian dan Pengabdian Kepada Masyarakat (UPPM) STIKES Dirgahayu Samarinda, 2025)
Adolescents in Indonesia face a triple burden of malnutrition, characterized by the co-existence of undernutrition, overnutrition, and micronutrient deficiencies. Dietary patterns and health, established during youth, are influenced by behavioral choices and environmental factors. Generally, adolescents are at risk of malnutrition, primarily due to high nutritional requirements that often conflict with their food choices and eating habits. This community service activity involved 35 female high school students residing at the Kartini Dormitory in Samarinda. The program was conducted by a team of lecturers from STIKES Dirgahayu Samarinda through discussion methods and physical examinations. The results indicated that the majority of female adolescents at the Kartini Dormitory were underweight based on Body Mass Index (BMI), totaling 15 individuals (43%), and the majority had a Mid-Upper Arm Circumference (LILA) of <23.5 cm, totaling 20 individuals (57%). BMI and MUAC are key indicators of nutritional status. The health education results showed a p-value of 0.00, signifying a significant change in the participants' knowledge regarding the importance of nutrition. Health education is a vital process to enhance the community's ability to maintain and improve their health status.